Nobiletin inhibits viability of human renal carcinoma cells via the JAK2/STAT3 and PI3K/Akt pathway - Xu, Zhenyu; Wu, Ding; Fu, Dian; Tang, Chaopeng; Ge, Jingping; Zhang, Zhengyu; Zhou, Wenquan (Cellular and Molecular Biology, 2020)
Nobiletin, a flavonoid found chiefly in oranges and lemons, has exhibited potential anti-proliferative and pro-apoptotic activities in various types of cancers. However, the inhibitory effect and mechanisms of nobiletin on renal cancer cells are unclear.  CCK8 and plate clone formation assay were used to determine the effect of nobiletin on the proliferation of renal cancer cells, while scratch healing test was used to assay its effect on migration ability. The effect of nobiletin on the invasion of renal cancer cells was determined using Trans well chamber assay. Flow cytometry was used to determine the effect of nobiletin on apoptosis of renal cancer cells, while Western blotting assay was used to determine its effect on the expressions of JAK2/STAT3 and PI3K/Akt pathway proteins, and apoptosis-related proteins. Nobiletin inhibited the proliferation of renal carcinoma cells in a time- and dose-dependent manner. It inhibited the migration and invasion of renal cancer cells, and promoted their apoptosis. Western blot results showed that nobiletin inhibited the phosphorylations of JAK2, STAT3, PI3K, and Akt, and promoted the expressions of apoptosis-related proteins. Nobiletin inhibits the proliferation, invasion and migration of renal cell carcinoma by inhibiting JAK2/STAT3 and PI3K/Akt pathways, and promotes their apoptosis. These findings provide a new experimental basis for the application of nobiletin in the treatment of renal cancer.